2018
DOI: 10.2147/ott.s167106
|View full text |Cite
|
Sign up to set email alerts
|

Protein tyrosine phosphatase L1 inhibits high-grade serous ovarian carcinoma progression by targeting IκBα

Abstract: BackgroundHigh-grade serous ovarian cancer (HGSOC) represents most of the ovarian cancers and accounts for 70%–80 % of related deaths. The overall survival of HGSOC has not been remarkably improved in the past decades, due to the tumor dissemination in peritoneal cavity and invasion of adjacent organs. Therefore, identifying molecular biomarkers is invaluable in helping predicting clinical outcomes and developing targeted chemotherapies. Although there have been studies revealing the prognostic significance of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 27 publications
1
10
0
Order By: Relevance
“…Unlike previous studies showing that PTPL1 controls NF-κB activation via p75NTR [ 43 ], we found that PTPL1 attenuates NF-κB activation by dephosphorylating IκBα at tyrosine 42 and consequently increasing the half-life of IκBα. These findings are in agreement with a recent report that PTPL1 could target IκBα in ovarian cancer cells [ 44 ]. Nonetheless, given the wide crosstalk between intracellular signaling pathways and the relatively low number of protein tyrosine phosphatases compared with protein tyrosine kinases, we cannot rule out that PTPL1 also regulates EnMT by targeting other pathways in vascular endothelial cells.…”
Section: Discussionsupporting
confidence: 94%
“…Unlike previous studies showing that PTPL1 controls NF-κB activation via p75NTR [ 43 ], we found that PTPL1 attenuates NF-κB activation by dephosphorylating IκBα at tyrosine 42 and consequently increasing the half-life of IκBα. These findings are in agreement with a recent report that PTPL1 could target IκBα in ovarian cancer cells [ 44 ]. Nonetheless, given the wide crosstalk between intracellular signaling pathways and the relatively low number of protein tyrosine phosphatases compared with protein tyrosine kinases, we cannot rule out that PTPL1 also regulates EnMT by targeting other pathways in vascular endothelial cells.…”
Section: Discussionsupporting
confidence: 94%
“…Previous studies have shown that three main kinases promote IκBα protein phosphorylation, namely IκB kinase (IKK), casein kinase II (CK2) and tyrosine kinase ( Perkins, 2006 ). The phosphatases that regulate IκBα dephosphorylation include calcineurin and protein tyrosine phosphatase L1 ( Pons and Torres-Aleman, 2000 ; Wang et al, 2018 ).…”
Section: Regulation Of the Phosphorylation/dephosphorylation Of Iκbαmentioning
confidence: 99%
“…Studies have revealed that calcineurin in astrocytes can be activated by insulin-like growth factor-I, which leads to site-specific dephosphorylation of p-Ser32, inhibition of IκBα degradation, and subsequent nuclear translocation of NF-κB p65 stimulated by TNF-α ( Pons and Torres-Aleman, 2000 ). In addition, the protein tyrosine phosphatase L1 inhibits the development of high-grade serous ovarian cancer through dephosphorylating p-Tyr42 to stabilize IκBα and attenuate the nuclear translocation of NF-κB ( Wang et al, 2018 ). Thyme quinone (a natural compound isolated from Nigella sativa ) can induce the release of superoxide anion and hydrogen peroxide in ABC cells which promoted IκBα dephosphorylation, arrested NF-κB p65 nuclear translocation, and finally inhibited the NF-κB pathway-mediated ABC cell survival pathway ( Hussain et al, 2013 ).…”
Section: Regulation Of the Phosphorylation/dephosphorylation Of Iκbαmentioning
confidence: 99%
“…These results were confirmed by Wang et al in a high-grade serous ovarian carcinoma (HGSOC) cell line (OV-90), in which PTPN13 transfection decreased the levels of IκBα phosphorylated at Y42 and of nuclear NF-κB, in contrast to transfection with PTPN13 siRNA. By using a siRNA against PTPN13 in combination with an inhibitor of IκBα phosphorylation or an IκBα mutant (Y42A), they confirmed that PTPN13 exerts its tumor suppressive effect by dephosphorylating IκBα at Tyr42 [ 89 ]. These results could provide a mechanistic explanation for the work by Castilla et al showing that PTPN13 and PKC-δ participate in NF-κB activation in PC3 prostate cancer cells [ 62 ] (see Section 2.1 ).…”
Section: Signaling Pathways and Biological Activities Affected By mentioning
confidence: 99%
“…In ovarian cancer, a first study of 95 specimens with different histological subtypes found no association between PTPN13 expression and survival at 2, 3, and 5 years [ 124 ]. However, two studies only on HGSOC, the most frequent ovarian cancer subtype, highlighted a correlation between high PTPN13 protein and mRNA expression and better prognosis in 97 and 58 HGSOC samples, respectively ( p = 0.042 and p = 0.03) [ 89 , 125 ]. They also observed that PTPN13 expression levels are reduced in tumor tissues compared with normal tissues.…”
Section: Medical Implication Of Ptpn13mentioning
confidence: 99%